Epidemiology of paediatric chronic fatigue syndrome in Australia. Issue 8 (23rd February 2019) - Knight, Sarah; Elders, Shane; Rodda, Jill; Harvey, Adrienne; Lubitz, Lionel; Rowe, Kathy; Reveley, Colette; Hennel, Sabine; Towns, Susan; Kozlowska, Kasia; Payne, Donald N; Marshall-Gradisnik, Sonya; et al.
Abstract : Objective: To estimate the paediatrician-diagnosed incidence of chronic fatigue syndrome (CFS) in Australia, and describe demographic and clinical features, as well as approaches to diagnosis and management. Methods: The Australian Paediatric Surveillance Unit facilitates monthly national surveillance of uncommon conditions seen by paediatricians. Data from young people aged <18 years diagnosed with CFS were collected. Incidence was estimated based on new cases reported from April 2015 to April 2016. Results: A total of 164 cases of newly diagnosed CFS in young people aged 4–17 years were identified for inclusion. The estimated national incidence for children aged 4–9 years was 0.25 per 100 000 per annum. In children aged 10–17 years, the estimated incidence of paediatrician-diagnosed cases for Victoria (17.48 per 100 000) was substantially greater than other Australian states (range 1.31–5.51 per 100 000). Most cases were female and Caucasian, most commonly presenting after an infectious illness with symptoms gradual in onset. The majority were diagnosed at least 13 months after symptom onset. Symptoms, associations, investigations and management strategies were highly variable. Conclusions: Current findings suggest that, consistent with other countries, the Australian incidence of CFS in children aged <10 years is very low. In contrast, the national incidence of CFS in older children and adolescents (aged 10–17 years) is more unclear, with marked variability between geographical regions apparent. This may be due to variation in service accessibility and clinician understanding of CFS. Accordingly, national initiatives to improve equity of care for children with CFS may be required.